Estudos dos efeitos de concentrações crescentes de óxido nitrico no processo de morte por perda de adesão ao substrato (Anoikis): o papel desempenhado no processo pela proteína Src quinase - Costa, Paulo Eduardo da [UNIFESP] (2017)
The study of cell death induced by loss of adhesion (anoikis) is essential to understand how metastatic tumor cells may develop resistance to this type of cell death. Among a number of factors that can influence anoikis, nitric oxide has your role little known in relation to this issue. In adhered cells, it is known that nitric oxide induces cellular proliferation at low concentrations, as well as induces cell death after the treatment with high concentrations. However, in our study, we observed that detached cells behave in a different mode when treated with increase concentrations of NO: Low concentrations of NO induces drop on cell viability in detached HeLa cells, as well as increase levels of cleaved caspase-3. Since high concentrations of NO induces anoikis protection, with increase on cell viability, decreased of caspase-3 cleavage and decrase of expression of Bim protein. Src kinase has been shown to have key role in this mechanism, being phosphorylated and nitrosylated following treatment with high concentrations of NO. Inhibition of Src, can reverse this protection induced by high concentrations of NO with respect to cell viability and expression of Bim protein.These viability results were reproduced in Nex8H metastatic melanomas, but not in non metastatic melanomas Nex10C. In HeLa cells kept in suspension, NO in high concentrations induced cell disaggregation in a Src dependent manner. NO-dependent disaggregation can be reproduced in murine melanoma cells Nex8H and Nex10C. Increasing concentrations of NO decreased the effectiveness of reattachment of HeLa cells kept in suspension. Src kinase showed no role in the process. We know that tumor cells often produce high concentrations of NO. This study shows up as a first step in understanding how these cells can migrate from a primary to a secondary source and got to readhere regarding the role of increasing concentrations of NO in the process.